Movie induced tourism: A new tourism phenomenon - Mijalce Gjorgievski; Sinolicka Melles Trpkova (UTMS Journal of Economics, 2012)
At the turn of the century, the tourism industry underwent a transformation triggered by the sweeping processes of globalization. The traditional forms of tourism were supplemented and expanded by the introduction of new postmodern tourist forms, bringing new and different tourist offers to the marketplace. One of these new forms is the film tourism, a rapidly growing and important new tourism trend, in which the choice of the tourist destination is directly motivated and inspired by the movies. Film tourism establishes a link between the movie characters, locations and stories, and the film-tourists, who are inspired to immerse themselves and relive again the movie-generated and movie-driven emotions at the location of the movie. The film tourism increases the overall economic effects of tourism and establishes a new link between the film and the tourism industry, both of which provide not only pleasure and satisfaction for the film tourist, but also spiritual enrichment and novel learning experience.
Keywords: L82; L83; 330; film; tourism; tourist; location; character; film studio